Examining the Effectiveness of Compassion-Based Acceptance and Commitment Integrated Therapy on Cortisol Hormone Levels and Mindfulness in Infertile Women Undergoing Hormone Therapy - Pourgoli, Sanaz; Dehghan, Maryam; Pourmohammad Ghouchani, Kamran; Naghshineh, Elham (Psychology of Woman Journal, 2026)
Objective: The purpose of this study was to investigate the effect of compassion-based acceptance and commitment integrated therapy on reducing cortisol hormone levels and improving mindfulness in infertile women undergoing hormone therapy. Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest control group. The statistical population consisted of infertile women undergoing hormone therapy in Isfahan, Iran, in 2023, from which 40 participants were selected using purposive sampling and randomly assigned to the experimental group (n = 20) and the control group (n = 20). The therapeutic intervention was conducted for the experimental group in 10 sessions. Research instruments included the Five Facet Mindfulness Questionnaire (FFMQ) and a salivary cortisol assessment test. Data were analyzed using multivariate analysis of covariance (MANCOVA) and multivariate analysis of variance (MANOVA). Findings: The results indicated that compassion-based acceptance and commitment therapy had a significant effect on reducing cortisol levels (P < .001) and improving various dimensions of mindfulness (P < .01). In the experimental group, the mean cortisol level decreased significantly in the posttest (a 2.2-unit reduction), while the control group showed a minimal, non-significant decrease. Moreover, overall mindfulness in the experimental group increased by 13.3 units; dimensions such as acceptance of negative emotions, present-moment focus, and non-judgmental awareness also demonstrated positive changes. MANOVA results further revealed that the difference between groups regarding the combination of dependent variables was significant (Wilks’ Lambda = 0.712, P < .001). Conclusion: The findings suggest that compassion-based acceptance and commitment integrated therapy is effective not only in reducing physiological stress (cortisol) but also in enhancing mindfulness skills.